Graphics design work: product / Afif Danish Momin - Momin, Afif Danish (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The “Sumpit” artwork analyses the characteristics of the sumpit from Iban ethnic in Sarawak through the understanding of media dimensions. The composition and unity as fundamental to the artwork in various media beyond the 'Sumpit', a multi-disciplinary undertaking that touches both printmaking, sculpture, painting and drawing to represent aspects irreducibly Sarawakian while revealing visual appeal across such varied arenas. Indigenous artwork concentrates on shape, space reflection, and cultural purpose.